PENERAPAN SISTEM PEMBUKTIAN TERBALIK TERHADAP TINDAK PIDANA KORUPSI (SEBUAH UPAYA PROGRESIF DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI) - Muwahid Muwahid (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractThe main object of this research is the regulation reversal burden of proof system of corruption in Act Number 20 of 2001. This research is a normative legal research, data obtained from primary legal materials that legislation, and secondary legal materials namely, books, journals and law relating to the burden of proof. The technique of data analysis uses content analysis.The results of research showed, First the reversal burden of proof system in criminal law of corruption stipulated in Article 12B paragraph (1), Article 37, Article 38A and Article 38B of Act Number 20 of 2001 on the eradication of corruption. Second, the application of reversal burden of proof principle in a criminal act of corruption is a specific provision in the law of criminal procedure, as a way to take war or eradicate of the corruption which is an extra ordinary crime, this provision is evidence of irregularities in the conventional system as was stipulated by the Criminal Code, in this case applies the principle of lex specialis derogat lex generalis.